AI for Improving Justice Delivery: International Scenario, Potential Applications & Way Forward for India - Srivastava, Sunil Kumar (Informatica, 2023)
Judiciary in India has been under tremendous pressure due to large number of cases pending at various levels. From time to time, several initiatives have been taken to reduce the backlog of pending cases in the courts. One of these is leveraging information and communication technology (ICT). Under this initiative (called e-Court), ICT solutions have been developed and deployed. This has led to visible improvement in the productivity. Even during the Covid-19 pandemic, the courts in India have been functioning. However, the number of pending cases has still been growing due to various reasons including increase in economic activities, awareness in the public and ease of access to the courts. The present work explores the possibility of using artificial intelligence (AI) in the processes to improve the justice delivery in India. A comprehensive literature survey was conducted to review the applications developed and deployed in this domain in other countries viz. Australia, Brazil, Canada, China, UK, and USA. Based on this, it identifies the gaps and suggests a spectrum of potential applications possible in Indian context. The article suggests a way forward for facilitating development and deployment of AI applications in this domain in India.